World Trade Organization {WTO} and the Caribbean financial service sector - Bissember, Enid E. (CCS GeorgetownGY, 1996)
Looks at the main issues in the General Agreement on Trade in Services (GATS) and the implications for the financial services sector in the Caribbean region. Focuses on issues such as control over international capital movement; market access; free movement of capital across the region; and, national treatment of foreign agents in the sector. Assesses the impact of liberalization on the economies of the region, and provides obervations, conclusions and recommendations.